Web services principles and technology - Papazoglou, M. 1953- (Pearson/Prentice Hall, 2008)
"This will be an informative guide for practice nurses, specialist community public health nurses, post registration nurses undertaking a programme of study leading to recording on the professional register, pre registration student nurses undertaking a programme of study leading to entry on to the professional register, nurses working in NHS Direct, nurses working in NHS walk in centres and nurses working in the prison setting."--BOOK JACKET.